Chapter 4 Kruder and Dorfmeister : The studio(us) remixers - Mazierska, Ewa (Taylor & Francis, 2018)
When Cruise , the film whose dialogue I used as an epigraph for this chapter, was released in 1970, these words were seen as capturing Polish inability to move beyond the safe zone of a well-known repertoire of images, melodies and symbols. Austrians allegedly are also stuck in the past (see Chapter 1 ). This would explain Kruder and Dorfmeister$1 (Bs penchant for making capital from our pleasure of listening to melodies we already know, if not for the fact that they gained fame not from capitalising on Vienna$1 (Bs music history but remixing songs coming from the Anglo-American centre of popular music, such as those by Depeche Mode, Madonna and David Holmes. Theirs is thus an interesting case of colonisation, which includes self-colonisation and reverse colonisation: taking something from the centre, reworking it and returning to the centre an improved version. Depending on the perspective, their productions can be seen as proof of the hegemony of the centre or a sign that the periphery can not only resist the centre$1 (Bs power but also penetrate it on its own terms. Equally, they can be seen as a sign of the end of authenticity and originality in popular music (and art at large) in the postmodern era or a need to rework these concepts to fit the art of creative recycling.s
English
Keywords: The arts; Electronica; Music; Austria; Vienna; History; Criticism; Popular music; Social aspects; Electronica; Music; Austria; Vienna; History; Criticism; Popular music; Social aspects; Brian Eno; Disc jockey; Kruder & Dorfmeister; Simon & Garfunkel